2023
DOI: 10.1063/5.0147456
|View full text |Cite
|
Sign up to set email alerts
|

Cooling dynamics of energized naphthalene and azulene radical cations

Abstract: Naphthalene and azulene are isomeric polycyclic aromatic hydrocarbons (PAHs) and are topical in the context of astrochemistry due to the recent discovery of substituted naphthalenes in the Taurus Molecular Cloud-1 (TMC-1). Here, the thermal- and photo-induced isomerization, dissociation, and radiative cooling dynamics of energized (vibrationally hot) naphthalene (Np+) and azulene (Az+) radical cations, occurring over the microsecond to seconds timescale, are investigated using a cryogenic electrostatic ion sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 91 publications
0
4
1
Order By: Relevance
“…Overall, there is little difference between the fragmentation mass spectra of az and nph in high-energy collisions, which may be due to the lower energy difference between multiply charged isomers compared to singly charged or neutral isomers. In a recent paper, Lee et al [26] demonstrated that even at much lower internal energies than in the present study, an equilibrium can be established between nph + and az + before dissociation. In fact, the energy transfer to the molecule is expected to be very high (typically few tens of eV) in collisional excitation with fast proton, so that the intact molecular ion can explore all available isomers prior to dissociation, independently from the initially chosen isomer.…”
Section: Single Hit Analysiscontrasting
confidence: 42%
“…Overall, there is little difference between the fragmentation mass spectra of az and nph in high-energy collisions, which may be due to the lower energy difference between multiply charged isomers compared to singly charged or neutral isomers. In a recent paper, Lee et al [26] demonstrated that even at much lower internal energies than in the present study, an equilibrium can be established between nph + and az + before dissociation. In fact, the energy transfer to the molecule is expected to be very high (typically few tens of eV) in collisional excitation with fast proton, so that the intact molecular ion can explore all available isomers prior to dissociation, independently from the initially chosen isomer.…”
Section: Single Hit Analysiscontrasting
confidence: 42%
“…31 and 32) prior to acetylene abstraction, is a seven member ring containing the isomer. This was recently reaffirmed independently by another group wherein it was concluded via analysis of kinetic energy release distributions measurements 54 that the ions accompanying acetylene abstraction was majorly pentalene with another minor product being phenylacetylene. Incidentally, these are the same products that are suggested to form after HCN abstraction from quinoline too.…”
Section: Discussionmentioning
confidence: 71%
“…There were no obvious marker m / z products from a given protomer ensemble that clearly reflect the protonation site, presumably because dissociation is statistical in nature and rearrangement barriers are lower in energy than dissociation barriers. 39…”
Section: Methodsmentioning
confidence: 99%